Catalytic carbon materials from biomass - Davies, Gareth; Ahmed, El Sheikh; Catherine, Collett; Ibrahim, Yakub; McGregor, James (Elsevier Inc., 2021)
Carbonaceous materials have a long history of application in heterogeneous catalysis. Their primary application has been as a support to disperse an active material—normally a metal or metal oxide. However, carbons can also act directly as catalysts, known as “carbocatalysts,” in a range of industrial processes.